Carbon Accounting and Sustainable Accounting: A Review - Thanya Ismiel Thanoon (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study reviews eight selected research articles on carbon accounting and sustainable accounting published between 2010 and 2024. The reviewed works explore various themes, including third-party roles in climate governance, adaptation strategies, environmental management accounting, corporate carbon reporting, net-zero carbon emissions, and sustainability integration in accounting frameworks. Despite differences in scope, sectoral focus, and methodological approach, all studies converge on three key insights: (1) the need to enhance understanding and management of carbon emissions and sustainability issues; (2) the importance of integrating sustainability metrics and strategies into business operations, reporting standards, and educational curricula; and (3) the urgency for more research and enabling frameworks that support the transition to a low-carbon economy. Notably, the studies vary in their contributions. Some adopt interdisciplinary perspectives, while others concentrate on sector-specific or methodological challenges, such as transparency, accountability, and the operationalization of sustainability practices. The research also reveals inconsistency in addressing research gaps—some areas remain predominantly empirical and require clearer definitions of causal relationships, whereas others demand theoretical development or applied knowledge for practical implementation. These gaps reflect the evolving nature of sustainability in accounting and highlight critical opportunities for future inquiry. Addressing these issues can support more effective carbon accounting practices and foster informed, strategic pathways toward sustainability.